Ketaatan, Ketidaktaatan, dan Keadilan dalam Negara Hukum: Perspektif Filsafat Politik Plato - Fatlolon, Costantinus (Sekolah Tinggi Filsafat Seminari Pineleng, 2024)
Laws are systematic rules that aim to guarantee citizen’s rights and freedom as well as to maintain social order. And yet, legal rules are often not obeyed because the essence and the law-making process do not provide a sense of justice to society. It raises a question: What is the principle for citizens to obey or disobey the law? Through an expository-critical approach, this article seeks to answer this question by reflecting Plato’s notion on obedience, disobedience, and justice in the state based on rule of law. It argues that justice is the main principle for citizens to obey or disobey the law since it is an architectonic principle which unify all other virtues. This theory has become an inspiration of the theory of law and the theory of civil disobedience in the modern democratic states.